Modeling carbon and water fluxes in agro-pastoral systems under contrasting climates and different management practices - L. Leolini; S. Costafreda-Aumedes; L. Brilli; M. Galvagno; M. Bindi; G. Argenti; D. Cammarano; E. Bellini; C. Dibari; G. Wohlfahrt; I. Feigenwinter; A. Dal Prà; et al. (Agricultural and Forest Meteorology, 2025)

Climate change impacts on two European crop rotations via an ensemble of models - E. Pohanková; P. Hlavinka; K.C. Kersebaum; C. Nendel; A. Rodríguez; J. Balek; J. Balkovič; M. Dubrovský; G. Hoogenboom; M. Moriondo; J.E. Olesen; J.W.M. Pullens; et al. (European Journal of Agronomy, 2025)

Expected effects of climate change on the soil organic matter content related to contrasting agricultural management practices based on a crop model ensemble for locations in Czechia - E. Pohanková; P. Hlavinka; K.C. Kersebaum; C. Nendel; A. Rodríguez; J. Balek; M. Dubrovský; A. Gobin; G. Hoogenboom; M. Moriondo; E.J. Olesen; R. Rötter; et al. (European Journal of Agronomy, 2024)

Uncertainties in the adaptation of alpine pastures to climate change based on remote sensing products and modelling - L. Brilli; R. Martin; G. Argenti; M. Bassignana; M. Bindi; R. Bonet; P. Choler; E. Cremonese; M. Della Vedova; C. Dibari; G. Filippa; M. Galvagno; et al. (Journal of Environmental Management, 2023)

Assessing climate change impacts on crops by adopting a set of crop performance indicators - M. Moriondo; M. Bindi; L. Brilli; S. Costafreda-Aumedes; C. Dibari; L. Leolini; G. Padovan; G. Trombi; A. Karali; K. V. Varotsos; G. Lemesios; C. Giannakopoulos; et al. (Euro-Mediterranean Journal for Environmental Integration, 2021)
The impact of climate change on the agricultural systems of three major islands in the Mediterranean basin, namely Sicily, Crete and Cyprus, was evaluated using a suite of specifically calibrated crop models and the outputs of a regional circulation model for Representative Concentration Pathway (RCP) 4.5 and 8.5 downscaled to 12 km of resolution and tested for its effectiveness in reproducing the local meteorological data. The most important annual (wheat, barley, tomato and potato) and perennial (grapevine and olive tree) crops were selected to represent the agricultural systems of the islands. The same modelling framework was used to test the effectiveness of autonomous adaptation options, such as shifting sowing date and the use of varieties with different growing season length. The results highlighted that, on average, warmer temperatures advanced both anthesis and maturity of the selected crops, but at different magnitudes depending on the crop and the island. Winter crops (barley, wheat and potato) experienced the lowest impact in terms of yield loss with respect to the baseline, with even some positive effects, especially in Sicily where both wheat and barley showed a general increase of 9% as compared to the baseline, while potato increased up to + 17%. Amongst perennial crops, olive tree showed low variation under RCP 4.5, but on average increased by 7% under RCP 8.5 on the three islands. Climate change had a detrimental effect specifically on tomato (− 2% on average in RCP 8.5 and 4.5 on the three islands) and grapevine (− 7%). The use of different sowing dates, or different varieties, revealed that for winter crops early autumn sowing is still the best option for producing wheat and barley in future periods on the three islands under both future scenarios. For tomato and potato, advancing sowing date to early winter is a winning strategy that may even increase final yield (+ 9% for tomato and + 17% for potato, on average). For grapevine, the use of late varieties, while suffering the most from increasing temperatures and reduced rainfall (− 15%, on average), is still a valuable option to keep high yield levels with respect to earlier varieties, which even if showing some increases with respect to the baseline have a generally much lower production level. The same may be applied to olive tree although the production differences between late and early varieties are less evident and climate change exerts a favourable influence (+ 4 and + 3% for early and late varieties, respectively).

Carbon sequestration capacity and productivity responses of Mediterranean olive groves under future climates and management options - L. Brilli; E. Lugato; M. Moriondo; B. Gioli; P. Toscano; A. Zaldei; L. Leolini; C. Cantini; G. Caruso; R. Gucci; P. Merante; C. Dibari; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

Projected shifts of wine regions in response to climate change - M. Moriondo; G. V. Jones; B. Bois; C. Dibari; R. Ferrise; G. Trombi; M. Bindi (Climatic Change, 2013)